Kinetics of Formation of Starch Microspheres Produced Using Aqueous Two-Phase Systems With Different Polymers in the Continuous Phase - Gidlöf, Zandra; Dobryden, Illia; Nilsson, Lars; Sommertune, Jens; Zhao, Wei; Wahlgren, Marie C. ; 0000-0002-1705-3964; Nordström, Randi; Millqvist-Fureby, Anna (Starch/Staerke, 2025)
Starch microspheres are employed in medicinal products as embolization agents and drug delivery vehicles. For the encapsulation of sensitive ingredients, mild cross-linking techniques are needed, prompting interest in physical cross-linking via starch crystallization. This study investigates starch microsphere formation and crystallization kinetics in aqueous two-phase systems (ATPS) with various continuous phase polymers, using confocal Raman microscopy, X-ray scattering, isothermal calorimetry, and light microscopy. The results showed that the solidification of starch particles depends on the ATPS polymers, being fastest in polyethylene glycol (PEG), followed by poly(2-ethyl-2-oxazoline) (PEtOx), and polyvinyl pyrrolidone (PVP). Confocal Raman microscopy can be used to follow the crystallization process, and its results match those from X-ray crystallography. Raman microscopy demonstrated uniform structural changes from amorphous to crystalline starch, with PEG and PEtOx facilitating faster crystallization than PVP. X-ray diffraction and isothermal calorimetry also demonstrated faster crystal growth and heat flow development in PEG and PEtOx formulations compared to PVP. Analysis of the kinetics using the Avrami model indicated that crystallization is uniform across the microspheres. Combining these results with light microscopy observations revealed that starch solidification occurs in the early stages of the crystallization process. In conclusion, the continuous phase polymer impacts the crystallization kinetics and structural evolution of starch microspheres, with PVP leading to slower crystallization compared to PEG and PEtOx. This suggests that polymer selection is crucial for tailoring the crystallization process of starch-based microspheres.
Keywords: isothermal calorimetry; kinetic of crystallization; Raman microscopy; starch microparticle; WAXS